Crohn's Disease of the Esophagus: Clinical Features and Treatment Outcomes in the Biologic Era. Issue 9 (September 2015) - De Felice, Kara M.; Katzka, David A.; Raffals, Laura E.
Abstract : Background: Esophageal Crohn's disease (CD) is challenging and often a disabling phenotype of disease. We aimed to report the clinical, endoscopic, histologic features, and treatment outcomes of esophageal patients with CD. Methods: Esophageal patients with CD evaluated at the Mayo Clinic in Rochester, MN, between January, 1998, and December, 2012, were identified. Results: Twenty-four cases of esophageal CD were identified. The median age of diagnosis was 23 years (range, 12–60). Twenty-one patients (88%) had extraesophageal CD and 8 patients (33%) had oral ulcers at the time of esophageal CD symptom onset. The majority of patients had esophageal-specific symptoms. Mid (29%) or distal (29%) esophagus was the most common site of involvement. Inflammatory esophageal CD (75%) was marked by superficial ulcerations (58%), erythema and/or erosions (50%), deep ulcerations (13%), and pseudopolyps (4%) on endoscopy. Four patients (17%) were found to have esophageal strictures and 2 patients (8%) had fistulizing disease. Chronic inflammation (83%) was seen on biopsy in the majority of cases with 5 patients having associated granulomas. In our series, inflammatory esophageal CD responded to prednisone, topical budesonide, or biologics. Stricturing esophageal CD was successfully treated with a combination of biologic therapy, immunomodulators, and serial dilations with/without steroid injections. Aggressive medical therapy with biologics and endoscopic therapy was used for fistulizing esophageal CD, however, was not universally effective. Conclusions: Esophageal CD should be considered in all patients with CD with upper gastrointestinal symptoms. Early recognition, diagnosis, and aggressive medical and/or endoscopic treatment are needed for successful outcomes. Abstract : Article first published online 16 June 2015.